2007
DOI: 10.1017/s1743921308014993
|View full text |Cite
|
Sign up to set email alerts
|

MHD mode conversion in a stratified atmosphere

Abstract: Mode conversion in the region where the sound and Alfven speeds are equal is a complex process, which has been studied both analytically and numerically, and has been seen in observations. In order to further the understanding of this process we set up a simple, one-dimensional model, and examine wave propagation through this system using a combination of analytical and numerical techniques. Simulations are carried out in a gravitationally stratified atmosphere with a uniform, vertical magnetic field for both … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Linear mode conversion on the other hand is more universal for magnetosonic waves [see e.g. Zhugzhda (1979); Zhugzhda & Dzhalilov (1981, 1982a; Cally (2001); McDougall & Hood (2007a,b, 2009 for similar linear mode conversion for magnetogravity waves at the magnetic canopy in solar chromosphere]. Finally, resonance can happen for Alfvén mode, where the well-known Alfvén resonance can generate secondary Slow and Fast waves [see Hollweg (1971) or Appendix-A, and simulation in Figure 3].…”
Section: Discussionmentioning
confidence: 99%
“…Linear mode conversion on the other hand is more universal for magnetosonic waves [see e.g. Zhugzhda (1979); Zhugzhda & Dzhalilov (1981, 1982a; Cally (2001); McDougall & Hood (2007a,b, 2009 for similar linear mode conversion for magnetogravity waves at the magnetic canopy in solar chromosphere]. Finally, resonance can happen for Alfvén mode, where the well-known Alfvén resonance can generate secondary Slow and Fast waves [see Hollweg (1971) or Appendix-A, and simulation in Figure 3].…”
Section: Discussionmentioning
confidence: 99%
“…In future we plan to extend the Cairns and Lashmore-Davies [3] method to two dimensions, allowing the quantity of conversion and transmission to be calculated, as has been done for an isothermal [2], and non-isothermal [4], one-dimensional model.…”
Section: Discussionmentioning
confidence: 99%
“…This method has the advantage that an exact analytical solution need not be known. This was extended to include a non-isothermal atmosphere [4], where it was found that the same conversion and transmission coefficients apply. Mode conversion around a two-dimensional, magnetic null point has also been investigated [5].…”
Section: Introductionmentioning
confidence: 99%